1998
DOI: 10.1038/sj.cdd.4400399
|View full text |Cite|
|
Sign up to set email alerts
|

Apoptosis induced by microinjection of cytochrome c is caspase-dependent and is inhibited by Bcl-2

Abstract: Microinjection of cytochrome c induced apoptosis in all the cell types we tested (IPC-81, Swiss 3T3, Clone 8 fibroblasts, NRK, H295, Y1, HEK 293). The apoptotic phenotype induced by injected cytochrome c was characterized by externalization of phosphatidyl serine, cell detachment from substratum and from neighbor cells, and had the classic ultrastructural features of membrane budding, chromatin condensation and cell shrinkage. Depending on the cell type and concentration of cytochrome c, the induction of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 28 publications
4
68
1
Order By: Relevance
“…Indeed, it has been reported that the levels of cytosolic cytochrome c required to trigger caspase activation differ in a cell typedependent manner. 38 In conclusion, although results from previous studies suggest that Drp1-mediated mitochondrial fission is required for cytochrome c release 4,6,[25][26][27] and apoptosis execution, 4,26 we observed that knock down of Drp1 selectively and partially prevents cytochrome c release, and that it delays but does not protect against Bax/Bak-mediated apoptosis. Thus, according to our results, Drp1-mediated fission appears dispensable and does not seem to be a prerequisite for apoptosis.…”
Section: Discussioncontrasting
confidence: 60%
“…Indeed, it has been reported that the levels of cytosolic cytochrome c required to trigger caspase activation differ in a cell typedependent manner. 38 In conclusion, although results from previous studies suggest that Drp1-mediated mitochondrial fission is required for cytochrome c release 4,6,[25][26][27] and apoptosis execution, 4,26 we observed that knock down of Drp1 selectively and partially prevents cytochrome c release, and that it delays but does not protect against Bax/Bak-mediated apoptosis. Thus, according to our results, Drp1-mediated fission appears dispensable and does not seem to be a prerequisite for apoptosis.…”
Section: Discussioncontrasting
confidence: 60%
“…cyC-induced cell death has been demonstrated in multiple cell types, 18,19 and the technique has proven useful in studies of bystander cell death. [4][5][6] In the Xenopus oocyte, intracellular injection of cyC leads to the rapid activation of caspases, changes in pigmentation, and a progressive loss of resting membrane potential.…”
Section: Cytochrome C Injection Induces Both Primary and Bystander Cementioning
confidence: 99%
“…For example, in many mitotic cells such as HeLa cells, HEK 293 cells, primary fibroblasts and naïve PC12 cells, the addition of cytochrome c to cytosolic extracts or injection of cytochrome c into the cytosol of these cells induces rapid caspase activation and apoptosis. [4][5][6][7][8] In contrast, cytochrome c, although necessary, is not sufficient to induce apoptosis in postmitotic cells such as sympathetic neurons, differentiated PC12 cells and cardiomyocytes. 2,5,9,10 Recently, the X-linked inhibitor of apoptosis protein (XIAP) was identified as the critical regulator of caspase activation in these postmitotic cells.…”
mentioning
confidence: 99%